The spirit level : why greater equality makes societies stronger - Wilkinson, Richard G., ....-; Pickett, Kate, ....- (New York : Bloomsbury Press, 2011)
It is a well-established fact that in rich societies the poor have shorter lives and suffer more from almost every social problem. The Spirit Level, based on thirty years of research, takes this truth a step further. One common factor links the healthiest and happiest societies: the degree of equality among their members. Further, more unequal societies are bad for everyone within them-the rich and middle class as well as the poor. The remarkable data assembled in The Spirit Level exposes stark differences, not only among the nations of the first world but even within America's fifty states. Almost every modern social problem-poor health, violence, lack of community life, teen pregnancy, mental illness-is more likely to occur in a less-equal society.Renowned researchers Richard Wilkinson and Kate Pickett lay bare the contradictions between material success and social failure in the developed world. But they do not merely tell us what's wrong. They offer a way toward a new political outlook, shifting from self-interested consumerism to a friendlier, more sustainable society. This eye-opening UK bestseller shows how one single factor--the gap between its richest and poorest members--can determine the health and well-being of a society. The authors also outline a new political outlook in which a shift from self-interested consumerism to a friendlier, more sustainable society is paramount.
Material success, social failure. The end of an era -- Poverty or inequality? -- How inequality gets under the skin -- The costs of inequality. Community life and social relations -- Mental health and drug use -- Physical health and life expectancy -- Obesity: wider income gaps, wider waists -- Educational performance -- Teenage births: recycling deprivation -- Violence: gaining respect -- Imprisonment and punishment -- Social mobility: unequal opportunities -- A better society. Dysfunctional societies -- Our social inheritance -- Equality and sustainability -- Building the future.
Includes bibliographical references (p. 312-342) and index.
Keywords: Gelijkheid